2015
DOI: 10.1111/ijd.12706
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of adipocytokines in psoriasis patients receiving tumor necrosis factor‐α inhibitors: results of a retrospective analysis

Abstract: Patients with psoriasis show an imbalance between pro- and anti-inflammatory adipocytokines, which is reduced but not normalized after administration of TNF-α inhibitors for 24 weeks. This partial rebalancing seems to be mainly related to a reduction in proinflammatory adipocytokines, rather than an increase in anti-inflammatory adipocytokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 30 publications
4
59
0
10
Order By: Relevance
“…About the possible biologics' action on adipocytokines' levels, Shibata et al [115] demonstrated an increased in adiponectin and IL-6 level after infliximab treatment. We have recently demonstrated that Adalimumab and Etanercept could be able to rebalance, but not normalize, adipocytokines' levels, mainly related to a reduction of pro-inflammatory ones rather than an increase of adiponectin [62] .…”
Section: The Effect On Psoriatic Therapies On Adipocytokinesmentioning
confidence: 99%
See 2 more Smart Citations
“…About the possible biologics' action on adipocytokines' levels, Shibata et al [115] demonstrated an increased in adiponectin and IL-6 level after infliximab treatment. We have recently demonstrated that Adalimumab and Etanercept could be able to rebalance, but not normalize, adipocytokines' levels, mainly related to a reduction of pro-inflammatory ones rather than an increase of adiponectin [62] .…”
Section: The Effect On Psoriatic Therapies On Adipocytokinesmentioning
confidence: 99%
“…A higher risk of developing insulin resistance and of MetS components is detected in patients affected by central obesity than patients with excess of subcutaneous fat [59][60][61] . The energy storage, the endocrine role and the partecipation in the immune system are three important actions of the VAT [62] . Thus, excess adipose tissue results in an unbalance between pro-and anti-inflammatory cytokines and the increased inflammatory stimuli is responsible for the starting of the persistent low-grade inflammation [4,58,59] .…”
Section: Psoriasis and Nafld: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Serum levels of TNF-α, IL-6, leptin, and resistin were found significantly higher (P <0.05) and serum adiponectin levels were significantly lower in patients with psoriasis than in controls (P<0.0001). Further, serum leptin level in men and women with psoriasis correlated positively with obesity (P<0.05) and was the only adipokines significantly decreased after TNF-α inhibitors treatment (P=0.0003) [17].…”
Section: Which Causes Comorbidities; Obesity or Psoriasis?mentioning
confidence: 88%
“…It was suggested that these cytokines can inhibit the synthesis of adiponectin (an anti-inflammatory adipokine) by the subcutaneous and visceral adipose tissue and can trigger psoriasis, metabolic syndrome and cardiovascular diseases [8]. In contrast, psoriasis patients found to have higher risks of incident obesity (HR 1.18; 95% CI 1.14- Metabolically, both psoriasis and obesity are associated with hypoadiponectinemia and hyperleptinemia, at statistical significance [17,18]. Adiponectin acts as anti-inflammatory adipokines involves in the regulation of numerous physiological functions and immune response.…”
Section: Which Causes Comorbidities; Obesity or Psoriasis?mentioning
confidence: 99%